QURANIC STORIES IN INTRODUCING MESSAGES AND VALUES: AN ANALYSIS ON THE STORY OF PROPHET YUSUF A.S. - Ab Halim, Asyiqin (Journal of Al-Tamaddun, 2016)
Stories or narratives are among the unique styles used in the Qur‘an which can be found in a variety of ways such as by using dramatic dialogue or characterization. They are not limited to one kind of narrative but many, for example accounts on the Prophets, people in the past and events occurred during the time of the Prophet Muhammad PBUH. Furthermore, the Qur‘an present them with message and values as well as lesson and a reminder to its readers. The story of Prophet Yusuf A.S. is the only story narrated specifically by the Qur‘an in one single surah, accommodates with beautiful and artistic style used in the surah with numbers of message and reminder to be pointed out. Hence, this article attempts to discuss and examine on how the Qur‘an uses stories in introducing message and values by focusing on story of Prophet Yusuf A.S in surah Yusuf.